Phage resistance of conditionally pathogenic intestinal microbiota bacteria in children with microbiocenosis disorders - N. V. Aleksanina; T. I. Tverdokhlebova (Журнал инфектологии, 2021)
Objective: to study the circulation and prevalence of phage-resistant strains among opportunistic enterobacteria, isolated from children with disorders of intestinal microflora, in relation to domestic preparations of bacteriophages.Materials and methods. A bacteriological study of the fecal microflora of the colon in 970 young children for dysbiosis was carried out. The sensitivity of 720 antibiotic-resistant strains of opportunistic enterobacteriaceae (S. aureus, K. pneumoniae, P. mirabilis and P. vulgaris, P. aeruginosa, E. coli, coagulase-negative staphylococci) isolated from children to domestic mono- and polyvalent drugs was studied (coliprotein, staphylococcal, Pseudomonas aeruginosa, purified Klebsiella pneumonia bacteriophage, “Sextafag”, Intesta bacteriophage). Determination of sensitivity to bacteriophages was carried out by the “sterile spot” method. Antibiotic sensitivity was determined by the disk diffusion method. Statistical processing of the results was carried out using the Microsoft Office Excel 2007 software package.Results. A large percentage of phage-resistant strains with low sensitivity to bacteriophages was revealed among opportunistic bacteria, amounting to 54,2%, with the highest circulation among coagulase-negative staphylococci, Proteus, Klebsiella (more than 50%). A significant spread of intestinal dysbiosis was established in young children (87,5%), characterized by a low content of bifidobacteria and a high level of allocation of opportunistic enterobacteria, including in associations.Conclusion. As a result of the studies, a significant prevalence of phage-resistant strains in children with dysbiosis was revealed, which indicates the need for preliminary determination of their sensitivity to bacteriophages in order to resolve the issue of their possible inclusion in the intestinal microflora correction system.